the PENGARUH KUALITAS PELAYANAN KEFARMASIAN TERHADAP KEPUASAN KONSUMEN PADA APOTEK STAR MEDIKA 1 DAN STAR MEDIKA 2: PENGARUH KUALITAS PELAYANAN KEFARMASIAN TERHADAP KEPUASAN KONSUMEN PADA APOTEK STAR MEDIKA 1 DAN STAR MEDIKA 2 - Ni Kadek Putri Satya Jayanti (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
Consumer satisfaction is an important indicator in assessing the quality of pharmaceutical services in pharmacies, where the appearance of the pharmacy, friendliness of the staff, drug information services, drug availability, and speed of service are the main factors that influence it. The purpose of this study was to determine the effect of pharmaceutical service quality on consumer satisfaction at Star Medika 1 Pharmacy and Star Medika 2 Pharmacy and to identify the most dominant service elements that influence consumer satisfaction. This study used a quantitative method with a descriptive approach and cross-sectional design, involving 120 consumers selected using purposive sampling techniques, where data were collected through questionnaires that had been tested for validity and reliability, then analyzed with the Spearman correlation test using the SPSS 24 application. The results of the study showed that all indicators of service quality had a positive effect on consumer satisfaction. The dimensions of drug availability with a correlation coefficient of r = 0.765 with a significance of 0.000, friendliness of officers with a correlation coefficient of r = 0.757 with a significance of 0.000, drug information service correlation of r = 0.733 with a significance of 0.000, speed of service with a correlation coefficient of r = 0.732 with a significance of 0.000. These four dimensions have the strongest correlation to consumer satisfaction. The results of the study at Star Medika Pharmacy 1 and concluded that the characteristics of respondents were dominated by women aged 31-40 years with private/self-employed jobs who tended to return to shop 2-5 times. All aspects of pharmacy services, especially drug availability, friendliness of officers, drug information service, and speed of service, have a very strong relationship (correlation of 0.7302) and have a positive effect on consumer satisfaction.